Tax Criminal Policy: Harmonizing Article 44c of Law Number 7 of 2021 with Articles 39 and 39a - Sanusi Sanusi (Penerbit Goodwood, 2026)
Purpose: This study examines the internal conflict created by Article 44C of Law Number 7 of 2021 on the Harmonization of Tax Regulations in Indonesia's tax-criminal regime, especially its relationship with Articles 39 and 39A of the General Tax Provisions Law. Research Methodology: This study uses normative legal research with statutory, conceptual, and case approaches. Primary legal materials include Law Number 7 of 2021, Law Number 6 of 1983 as repeatedly amended, Government Regulation Number 50 of 2022, and Minister of Finance Regulation Number 177/PMK.03/2022. Secondary materials consist of reputable international journal articles, OECD materials, official Directorate General of Taxes releases, and selected court-based tax crime materials. Results: The analysis finds that Article 44C strengthens the fiscal recovery orientation of tax-criminal enforcement by making criminal fines non-substitutable through imprisonment and requiring actual payment by convicted offenders. However, when read together with Articles 39 and 39A, the provision may generate doctrinal tension between deterrence, proportionality, corporate criminal liability, enforceability of high fines and legal certainty. Conclusions: Harmonization should not be understood only as higher penalties but as an integrated architecture of legality, restorative fiscal recovery, due process, and credible enforcement. Limitations: This study is doctrinal and does not statistically measure sentencing outcomes. Contributions: This study contributes to Indonesian tax-criminal law scholarship by proposing a harmonized interpretation of Article 44C based on legality, proportionality, and revenue protection.